Identidade e imaginária Jesuítico-Missioneira da redução de São Francisco de Borja: altares particulares, da idolatria ao fogo. - Rodrigues, José Fernando Corrêa (2019)
This research aimed to analyze the jesuitic-missionary imaginary from the old São Francisco de Borja Reduction, comparing photographically some examples of religious imaginaries by private owners catalogued in 1989/1992, for which original inventories are kept by IPHAN (National Historic and Artistic Heritage Institute), in order to develop a traveling exhibition with the findings of the research. We sought to interpret the remaining cultural heritage from the Reductions period found in São Borja, and we relate the concepts of identity and cultural heritage to the history of imaginary resistance existing in the mentioned municipality. We purpose to amplify the local community knowledge regarding their own origin and cultural heritage, with the history of imaginary resistance existing in the said municipality, we propose to broaden the knowledge of the São-Borja community. As resulting product of this research, we developed a traveling exhibition composed by fifteen banners which will be inaugurated in Apparício Silva Rillo Municipal Museum, in the city of São Borja, in 2019.